Ambroxol-Enhanced Frequency and Amplitude of Beating Cilia Controlled by a Voltage-Gated Ca2+ Channel, Cav1.2, via pHi Increase and [Cl−]i Decrease in the Lung Airway Epithelial Cells of Mice - Nakahari, Takashi; Suzuki, Chihiro; Kawaguchi, Kotoku; Hosogi, Shigekuni; Tanaka, Saori; Asano, Shinji; Inui, Toshio; Marunaka, Yoshinori (International journal of molecular sciences, 2023)
Ambroxol (ABX), a frequently prescribed secretolytic agent which enhances the ciliary beat frequency (CBF) and ciliary bend angle (CBA, an index of amplitude) by 30%, activates a voltage-dependent Ca2+ channel (CaV1.2) and a small transient Ca2+ release in the ciliated lung airway epithelial cells (c-LAECs) of mice. The activation of CaV1.2 alone enhanced the CBF and CBA by 20%, mediated by a pHi increasei and a [Cl−]i decrease in the c-LAECs. The increase in pHi, which was induced by the activation of the Na+-HCO3− cotransporter (NBC), enhanced the CBF (by 30%) and CBA (by 15–20%), and a decrease in [Cl−]i, which was induced by the Cl− release via anoctamine 1 (ANO1), enhanced the CBA (by 10–15%). While a Ca2+-free solution or nifedipine (an inhibitor of CaV1.2) inhibited 70% of the CBF and CBA enhancement using ABX, CaV1.2 enhanced most of the CBF and CBA increases using ABX. The activation of the CaV1.2 existing in the cilia stimulates the NBC to increase pHi and ANO1 to decrease the [Cl−]i in the c-LAECs. In conclusion, the pHi increase and the [Cl−]i decrease enhanced the CBF and CBA in the ABX-stimulated c-LAECs.